Beyond Brexit – Is the UK's Fixed Quota Allocation (FQA) system in need of a fix?. (July 2021) - Forse, Andy; Drakeford, Benjamin; Failler, Pierre; Potts, Jonathan; Akbari, Negar
Abstract: This paper presents the results of interviews conducted with stakeholders in the North East Scotland commercial fishing industry who operate with Fixed Quota Allocation (FQA) units under the United Kingdom's (UK's) fisheries management system. The results derived from these interviews provide a view of the FQA system from those operating within it and identify strengths and weaknesses of the system. The implications of these results are that the FQA system, and the introduction of FQA units, led to increased investment and efficiency within the North East Scotland 'over 10 m′ sector. This, however, has led to a consolidation of quota and the raising of barriers to entry. These may threaten the future of the industry and its traditional links to its coastal communities but the situation is complicated by concerns that any changes to the system to address these threats risks destabilising the economic structure of the industry which is built on the asset value of FQA units. The UK Government has indicated that the system will endure post-Brexit so it may be that any additional quota realised from exiting the European Union (EU) is applied to a system where those who will benefit most understand that it may risk the industry's future. This paper calls for more research into the FQA system, with those who work with FQA units and those who do not, to ensure that the socioeconomic impacts of this system are better understood in order that future management safeguards the stability of the industry into the future. Highlights: FQA units attracted investment to 'over 10m' in North East Scotland, industry now reliant on system existing in perpetuity. FQA units have driven efficiency in the 'over 10m' sector but have led to consolidation and raised barriers to entry. Brexit may benefit 'over 10m' sector but will not address the issues within the FQA system.